High-capacity ammonium tetravanadate (NH4V4O10) as non-aqueous magnesium-ion battery cathode material - Esparcia, Eugene Jr
The magnesiation/demagnesiation capability of ammonium tetravanadate, NH4V4O10, as cathode material in magnesium-ion (Mg-ion) battery using dry organic electrolyte is demonstrated. Synthesized via hydrothermal reaction, NH4V4010 forms nanobelts and shows reversible intercalation as cathode, with initial discharge and charge capacity at 0.2 C-rate of 174.8 mAh g-1 and 204.6 mAh g-1 respectively, and an open circuit potential (OCP) of around 2.92 V (v5. Mg/Mg2). The extra initial charge capacity is attributed to deammoniation, as confirmed via XRD and FTIR analysis. The NH4V4010-based cathode exhibits a capacity retention at 1C of 36.8 mAh g-1 after 100 cycles. The magnesiation/demagnesiation process was verified using elemental analysis in Energy dispersive x-ray spectroscopy (EDX), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), with Mgo.79NH4V4010 as the magnesiated chemical formula, corresponding to the partial reduction of to partial reduction of V5+ to V4+.